2019
DOI: 10.1029/2018ja026378
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Properties of Magnetospheric Line Radiation and Quasiperiodic Emissions on Solar Wind Parameters and Geomagnetic Activity

Abstract: Very low frequency electromagnetic waves in the inner magnetosphere sometimes exhibit either frequency or time modulation. These phenomena are called, respectively, magnetospheric line radiation (MLR) and quasiperiodic (QP) emissions. Data from Detection of Electro-Magnetic Emissions Transmitted from Earthquake Regions spacecraft were used to analyze their properties, such as MLR frequency spacing, QP modulation period, and QP intensity as functions of geomagnetic activity and solar wind parameters. Altogether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
(78 reference statements)
1
7
0
Order By: Relevance
“…However, this QP classification was based on ground-based measurements and, as shown by Tixier and Cornilleau-Wehrlin (1986), it is not straightforward to apply to spacecraft observations, rendering it somewhat unclear (Sazhin & Hayakawa, 1994). Additionally, Bezděková et al (2019) reported that properties of QP emissions with short (<∼20 s) and long (>∼20 s) modulation periods react differently to geomagnetic activity, suggesting that they might be generated by different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, this QP classification was based on ground-based measurements and, as shown by Tixier and Cornilleau-Wehrlin (1986), it is not straightforward to apply to spacecraft observations, rendering it somewhat unclear (Sazhin & Hayakawa, 1994). Additionally, Bezděková et al (2019) reported that properties of QP emissions with short (<∼20 s) and long (>∼20 s) modulation periods react differently to geomagnetic activity, suggesting that they might be generated by different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…MLR events occur more often on the dayside than the night side, and their location is mostly at regions of L > 2 but typically inside the plasmasphere. Additionally, their occurrence primarily depends on disturbed space weather conditions (Bezděková et al., 2019; Parrot et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relatively straightforward measurement technique used for their detection, they have been studied on the ground for more than 60 years (Helliwell, 1965). However, while their detection provides a remarkable amount of information about the magnetosphere, generation mechanisms, properties, and means of propagation of many of the observed wave phenomena are not yet fully understood (e.g., Bezděková et al., 2019; Breuillard et al., 2014; Green et al., 2005; Manninen, 2005; Rodger et al., 2000). Hence, they are still in the scope of intense research.…”
Section: Introductionmentioning
confidence: 99%